Analysis in the recognition, measurement and disclosure of income from services for hotel SMEs in the ecotourism sector based on IFRS for SMEs (GEON Journal (Management, Organizations and Business), 2021)
Problematic: After the implementation of the IFRS regulatory framework for SMEs in Colombia, hotel companies in the ecotourism sector have shown significant economic growth, which has increased its competitiveness and business productivity; however, there are few bibliographic references to allow the analysis of those effects. Objectives: the purpose is to analyze the methods used by these companies to recognize, measure and report revenues from ordinary activities for guest accommodation services. Materials and methods: the methodology used is a dynamic one that includes a documentary review of the legal and regulatory accounting framework, academic repositories, and the analysis of official reports, applying an exploratory and explanatory investigation of the current technical regulatory framework, using a mixed quantitative and qualitative research approach. Results: Revenues from hotel services are made according to Decrees 2706 of 2012 and 3022 of 2013. The revenues are recognized when a credible measurement can be made and the control, risks, and benefits of the good or customer service are transferred. Its measurement is based on fair value applying the active market method. Discussion: The implementation of section 23 of IFRS for SMEs has not affected the economic performance of SMEs in the ecotourism sector; instead, it has generated greater foreign investment and capital flows. Conclusions: Companies of groups two and three apply IFRS for SMEs, which may incorporate section 23 into its individual policies. Contribution/originality: It is expected to formulate an implementation guide for the accounting standard for the recognition, measurement, and disclosure of service revenues for hotel companies in the ecotourism sector that meet the requirements to apply IFRS group two and, in the case of microenterprises in group three, if they wished, they would be able to incorporate section 23 into their individual policies.
Keywords: Accounting; Economic growth; Ecotourism; Hotel industry; Income; International Financial Reporting Standards (IFRS); IFRS; Small companies; Tourism industry